(untitled) (Bangladesh Heart Journal, 2022)
Introduction: Left main disease (LMD) is related to significant morbidity and mortality. This study was done to evaluate the clinical major adverse cardiovascular event (MACE), including unstable angina, myocardial infarction, heart failure, target vessel revascularization, stroke and death in patients undergoing left main stem stenting without availability of in-site intravascular imaging (IVUS). Methods & Materials: It was a prospective observational study done in National Institute of Cardiovascular Diseases & Hospital (NICVD) from March 2014 to June 2019. Our study included 50 patients who underwent Percutaneous Coronary Intervention for left main disease without use of IVUS. All the patients were followed up for 1 year & 2 years, one patient was lost to follow-up. Outcomes included in MACE were death, myocardial infarction, unstable angina, heart failure, stroke and target vessel revascularization (TVR). Results: Fifty patients (mean age 58.4 ± 4.1 years, 44 male, 06 female) were treated with a mean SYNTAX score of 24.8 ± 2.6. Thirty two (64%) patients had stable angina, 17 (34%) had unstable angina/non ST-elevation myocardial infarction, and 1 (02%) had ST-elevation Myocardial infarction. Among the risk factors, 21(42%) had DM, 33 (66%) were hypertensive, 22 (44%) were smoker, 19 (38%) had dyslipidemia, 09 (18%) had previous h/o MI, 11 (22%) had family h/o CAD & 01 (02%) had previous h/o CVD. Preprocedural LVEF was 49.92± 6.60 % and post procedural 54.84 ± 4.55% which showed significant improvement of LVEF after PCI (p=0.003). Most of the patients presented with LM with SVD (82%). Among all patients, 39 (78%) underwent complete revascularization in compare to 11 (22%) had incomplete revascularization. Thirty eight (76%) patients received a single-stent DES and 12 (24%) received two-stents DES. Among double stent strategy, majority underwent TAP (50%). All access was femoral & No reflow phenomena were found in any of the patients during the procedure. No perioperative mortalities were noted and no urgent coronary bypass graft surgery was required. One patient was lost to follow-up. After 1-year follow-up period, 1 (02%) patients had non-fatal myocardial infarction, 7 (14%) had episodes of unstable angina (UA) and 3 (06%) had heart failure (HF). After 2-years there was no new MI but 09 (18%) had UA & 4 (08%) patients had HF episode in total. TLR was 2 (04%) in first year and 3 (06%) in 2nd year. Total mortality was 1(02%) in first year & 3(06%) in 2nd year. The multivariable analysis showed a good prognosis in patients receiving LM PCI with a total event rate of 28% & mortality 6%. A multivariate regression analysis with risk factors for coronary artery disease as predictive variables showed that high SYNTAX score (p = 0.013), incomplete revascularization (p=0.002) & low post procedural LVEF (p= 0.001) was an independent predictor of MACE. Conclusion: Percutaneous coronary intervention of left main coronary disease without use of IVUS showed good prognosis after 1-year & 2-years follow-up. It would not only save a procedure time for physicians but also prevent a financial burden on patients if they cannot afford intravascular imaging. Bangladesh Heart Journal 2022; 37(1): 1-9